ЕЛЕКТРОТЕХНІЧНА СИСТЕМА З ЧАСТОТНО-ПАРАМЕТРИЧНИМ РЕГУЛЮВАННЯМ СТАБІЛІЗОВАНОГО РОЗРЯДНОГО СТРУМУ У ВУГЛЕЦЕВМІСНИХ ГАЗАХ - Винниченко, Д.В.; Назарова, Н.С. (Інститут електродинаміки НАН України, Київ, 2019)
The combined method of frequency-parametric regulation of the stabilized current of the power source is developed on the basis of the resonant inverter for real-time providing of the optimal value of the discharge current during the change of the length of the inter-electrode gap. According to this method, to provide a given output current stabilization factor, an automatic transition from thecontinuous current control is performed by changing the frequency of the inverter to the discrete regulation of the natural frequencyof the resonant circle due to the switching of the inductors. The usage of this method ensures current stabilization up to 99% in the case of the active linear load and 95% in the case of the electro-discharge load. References 12, figures 3.